P765Diabetic cardiomyopathy: a comparative investigation in diabetic rat models. (15th July 2014) - Matyas, C; Korkmaz, S; Olah, A; Nemeth, BT; Hidi, L; Birtalan, E; Torok, M; Merkely, B; Szabo, G; Radovits, T
Abstract: Purpose: Diabetic cardiomyopathy, a cardiac manifestation of diabetes mellitus (DM), is characterised by specific structural, molecular and functional alterations of the myocardium. Upon this concept we investigated whether type-1 or type-2 diabetes lead to different alterations in cardiac function or histological and molecular changes. Methods: Our experiments were carried out in a rat model of type-1 (streptozotocin induced) and type-2 DM (Zucker Diabetic Fatty rats). Left ventricular (LV) function was characterised using a pressure-volume (P-V) conductance catheter system. Load independent indices of LV contractility (preload recruitable stroke work (PRSW)) and indices of LV relaxation (time constant of LV pressure decay(Tau)) and stiffness (LV end-diastolic pressure (LVEDP)) were calculated, respectively. In addition to our functional measurements TUNEL assay was performed to evaluate degree of apoptosis. Myocardial gene expression analysis was performed by qRT-PCR, expression of proteins was investigated by western blot and immunohistochemistry. Results: In comparison to the control, type-1 DM resulted in decreased LV systolic performance: decreased systolic pressure, maximal dP/dt and PRSW (45.39±2.45 vs 76.44±4.06 mmHg). Type-2 DM was associated with increased LV stiffness (LVEDP: 9.4±0.5 vs 7.7±0.4 mmHg) while systolic indices were altered only to a lower extent. We observed cardiac hypertrophy and degeneration with histomorphological examination. More pronounced nitro-oxidative stress resulted in more severe DNA-damage. Overexpression of c-fos and c-jun and downregulation of eNOS were observed in type-1 diabetic rats. On the other hand TGF-β1 and ANF mRNA-levels were significantly higher in type-2 diabetic model. Conclusions: Diabetic cardiac alterations are characterised by decreased systolic performance and impaired relaxation in type-1 diabetic rats, while diastolic dysfunction was more pronounced in type-2 DM. In the background of diabetic cardiomyopathy different processes can be identified in the two models.